Physiological and physical characteristics of BMX freestyle athletes: a preliminary review - Liang, Weibao; Hou, Yu; Liu, Chuannan; Ma, Shuhui; Zong, Yue; Yan, Xujie (Frontiers in Physiology, 2025)
BMX Freestyle, a newly recognized Olympic discipline, demands athletes perform intricate, high-intensity maneuvers during 60-s competitive runs. Despite the sport’s rapid evolution, there is a notable scarcity of scientific investigation into the distinct physiological and physical attributes of its athletes. This preliminary review synthesizes the extant literature to delineate the key physiological and physical characteristics of BMX Freestyle athletes and to identify pressing directions for future research. Elite male athletes typically present with lower body fat percentages, contributing to an advantageous power-to-weight ratio. Physiologically, these athletes demonstrate substantial anaerobic power, crucial for executing aerial maneuvers and complex rotational skills. Maximal oxygen uptake (VO2max) is typically moderate, likely facilitating inter-competition recovery and the capacity to sustain demanding training regimens. Musculoskeletally, athletes require high lower-limb explosive power for jump amplitude, significant upper-body strength for bike control and landing impact attenuation, and robust core musculature for executing complex aerial rotations. Furthermore, highly developed neuromuscular control, including dynamic balance, precise muscle activation patterns, and coordination, is foundational for performing advanced skills. This synthesis provides an evidence-based framework for optimizing training protocols focused on explosive power and eccentric strength, developing quantitative talent identification models, and implementing targeted injury prevention strategies that address the unique demands of the human-bicycle interface. Future research should focus on validating these applications and investigating the characteristics of female competitors to advance athlete health and performance in this evolving Olympic sport.